Seven days and seven nights - Shyamanta Das; Samrat Singh Bhandari (Open Journal of Psychiatry and Allied Sciences, 2022)
The editorial narrates the experience of treating symptomatic Covid-19 patients admitted in a tertiary care general hospital.